Associations between CES1 variants and dosing and adverse effects in children taking methylphenidate - Brown, Jacob T.; Beery, Nancy; Taran, Allise; Stevens, Tyler; Henzler, Christine; Badalamenti, Jonathan; Regal, Ron; McCarty, Catherine A. (Frontiers in Pediatrics, 2023)
Background Methylphenidate is the most prescribed stimulant to treat attention deficit-hyperactivity disorder (ADHD). Despite its widespread usage, a fair proportion of children are classified as non-responders to the medication. Variability in response and occurrence of adverse events with methylphenidate use may be due to several factors, including drug-drug interactions as well as pharmacogenetic differences resulting in pharmacokinetic and/or pharmacodynamic variances within the general population. The objective of this study was to analyze the effect of carboxylesterase 1 (CES1) variants on the frequency of adverse effects and dosing requirements of methylphenidate in children with ADHD. Methods This was a retrospective cohort study of children and adolescents who met the inclusion criteria and had a routine visit during the enrollment period were invited to participate. Inclusion criteria included: ADHD diagnosis by a healthcare provider, between 6 and 16 years of age at the time of permission/assent, had not previously been prescribed methylphenidate, and treatment with any methylphenidate formulation for at least three consecutive months. Three months of records were reviewed in order to assess changes in dose and frequency of discontinuing methylphenidate. Participants’ ADHD symptoms, medication response, adverse effects, select vitals, and dose were extracted from the electronic health record. Saliva samples were collected by trained study coordinators. Haplotypes were assigned based on copy number in different portions of the CES1 gene. Due to limited numbers, diplotypes (combinations of two haplotypes) were grouped for analysis as CES1A1/CES1A1, CES1A1/CES1A1c and CES1A1c/CES1A1c. Results A total of 99 participants (n = 30 female; n = 69 male) had both clinical data and CES1 sequencing data, with an average age of 7.7 years old (range 3–15 years). The final weight-based dose in all individuals was 0.79 mg/kg/day. The most common adverse effects reported were decreased appetite (n = 47), weight loss (n = 24), and sleep problems (n = 19). The mean final weight-based dose by haplotype was 0.92 mg/kg for CES1A2/CES1A2, 0.81 mg/kg for CES1A2/CES1P1, and 0.78 mg/kg for CES1P1/CES1P1. After correction for multiple hypothesis testing, only one SNV, rs114119971, was significantly associated with weight-based dosing in two individuals. The individuals with the rs114119971 SNV had a significantly lower weight-based dose (0.42 mg/kg) as compared to those without (0.88 mg/kg; p < 0.001). Discussion Variation in CES1 activity may impact dose requirements in children who are prescribed methylphenidate, as well as other CES1 substrates. Although intriguing, this study is limited by the retrospective nature and relatively small sample size.